Industrial Internet of Things (IIoT): Trends and Technologies - Zhihao Liu; Franco Davoli; Davide Borsatti (Future Internet)
The Industrial Internet of Things (IIoT) integrates sensors, machines, and data processing in industrial facilities to enable real-time monitoring, predictive insights, and autonomous control of equipment [...]